2016
DOI: 10.5897/ajar2016.11061
|View full text |Cite
|
Sign up to set email alerts
|

Saline water and organic matter in the development and quality of Licania rigida Benth. seedlings

Abstract: Licania rigida Benth. (oiticica) is a native species from the Northeastern Brazil. In this sense, the aim of this study is to evaluate the effects of irrigation with saline water and organic matter on the growth and quality of oiticica seedlings. The experiments were laid out in randomized complete block using a 5 × 2 factorial design related to electrical conductivity of irrigation water at 0.5, 1.5, 3.0, 4.5 and 6.0 dS m -1 in a substrate with and without organic castor bean compost (Ricinus communis) and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This behavior of oiticica seedlings irrigated with brackish water in substrate supplemented with composted bovine manure and castor bean and potassium differs from that presented by Diniz Neto et al ( 2014) who found that all biometric growth and quality variables were significantly influenced by the interaction between sources of variation. In contrast, our results are in agreement with Cavalcante et al (2016) who concluded that oiticica seedlings did not respond to the interactive effects of water-salinity × organic matter, but were rather influenced the independent effects of each source of variation.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This behavior of oiticica seedlings irrigated with brackish water in substrate supplemented with composted bovine manure and castor bean and potassium differs from that presented by Diniz Neto et al ( 2014) who found that all biometric growth and quality variables were significantly influenced by the interaction between sources of variation. In contrast, our results are in agreement with Cavalcante et al (2016) who concluded that oiticica seedlings did not respond to the interactive effects of water-salinity × organic matter, but were rather influenced the independent effects of each source of variation.…”
Section: Resultssupporting
confidence: 93%
“…Seedling total dry mass in the 1OM:1S, 2OM:1S, and 3OM:1S substrates was, respectively, 29.7, 28.4, and 63.5% greater than seedlings grown in a substrate free of organic matter (Figure 5). When considering the supremacy of the seedlings, of the respective treatments, in relation to the substrate without organic compound, the positive action of this input in the reduction of the harmful effects of water salinity on the formation of oiticica seedlings, as recorded per Cavalcante et al (2016) and Cavalcante et al (2020) in seedlings of the same species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation